Choosing a Path of Life According to the Concept of Human Nature in Education - Mulyadi, Mulyadi; Bustam, Betty Mauli Rosa (Al Hikmah: Journal of Education, 2024)
This research will discuss why there are still deviations committed by believers in qadha and qadar without awakening their enthusiasm to pursue happiness in this world and the hereafter. The approach used in this research is a qualitative descriptive approach to describe situations or phenomena by examining symptoms, information or result information during the research process using the document study method. Literature research data collection methods consisting of daily articles, textbooks, handbooks, archives and regulations and journals, etc. Researchers analyze the influence of belief in qada' and qadar and impose it on ghiroh to carry out a transformation of its exclusive destiny within the scope of Islamic religious education. The results of this research indicate that the occurrence of behavioral deviations carried out by believers in qadha and qadar who have not awakened their enthusiasm to pursue happiness in this world and the hereafter is due to a wrong understanding of faith in qadha and qadar, because the stronger their faith, the more enthusiastic they will be in pursuing worldly happiness. in the afterlife, with intelligence being able to develop and think clearly to consider, decide and face things by focusing on the problems faced with brilliant solutions, so that it will form a personality that is confident, not worried, brave, optimistic, full of hope.